Odzivanje na komplesno! varnostno krizo v Sloveniji - Malešič, Marjan (Teorija in praksa, 2008)
The article is based on presumption that contemporary security crises are increasingly explicitly marked by quantity growth and important quality changes displayed by endemicity of crises, their composition, duration and complexity. Tendency of big contemporary crises is that their effect goes beyond the state borders, that they expand from one social field to another, and that they connect with the existing social problems which become more aggravating. The changing dimensions of modern crises have direct influence on crisis management. Its conventional organisation and co-ordination forms are not adequate anymore, a rethinking of politics and capacity of crisis response is needed which would take into account national as well as international level of the problem. The stated characteristics of the crisis and crisis management are also a concern of Slovenia, which has a relatively well-developed crisis management within individual governmental agencies, but has not yet established appropriate coordination between them, i.e. on the national, strategic level. The article is composed of short theoretical introduction of crisis and crisis management; results of analysis of legal structure, which regulate this field in Slovenia; subjective viewpoint of management structure on crisis management and final conclusions.
Keywords: Crises; Krize; Crisis management; Krizno upravljanje; Leadership; Vodenje; Nacionalna varnost; National security; Slovenia; Slovenija; politično odločanje; krizni management